JasperReports 3.5 for Java developers : create, design, format, and export reports with the world's most popular Java reporting library - Heffelfinger, David R. (From technologies to solutions., 2009)
"The book has been fully updated to use JasperReports 3.5, the latest version of JasperReports. Previously accepted techniques that have now been deprecated have been replaced with their modern counterparts. All examples in the book have been updated to use XML schemas for report templates. Coverage of new data sources that JasperReports now supports has been added to the book. Additionally, JasperReports can now export reports to even more formats than before and exporting reports to these new formats is covered in this new edition of the book. Starting with the basics of adding reporting capabilities to your application and creating report templates, you will first see how to produce your reports through the use of JRXML files, custom ANT targets, and then preview them in both the web browser and the native browser of JasperReports. All examples have been updated to use XML schemas. New export formats, such as OpenDocument Text, and new data sources now supported by JasperReports are now covered in this updated edition"--Resource description page.